Invited review: Limitations to current mineral requirement systems for cattle and potential improvements - W.P. Weiss; S.L. Hansen (Journal of Dairy Science)
ABSTRACT: The mineral requirements or recommendations generated by various NASEM committees are used by many ration formulation programs. The current NASEM dairy requirement system uses the factorial approach (requirements for maintenance, lactation, gestation, and growth) for most minerals, but when data or equations were not available to estimate factorial requirements the committee used available data to estimate adequate intake values. The current beef NASEM uses the factorial method for Ca and P and recommendations for the other minerals. The factorial method works well for Ca and P because adequate data are available to estimate absorption coefficients (AC) and maintenance requirements. In addition, feeding Ca and P above requirements has few if any positive effects. For many other minerals the factorial method is problematic. Estimating both the maintenance requirement and AC can be extremely difficult and inaccuracies in those values have a major impact on accuracy of total dietary requirements. Some minerals have positive effects on health, production, and reproduction when fed above factorially determined requirements. For those minerals, response models rather than or in addition to requirement models are more appropriate. The AC is in the denominator of the factorial equation and converts absorbed requirements into dietary requirements. The AC for trace minerals is small, often <0.1, and small changes in a low AC can have substantial effects on dietary requirements. Although accurate AC are essential for the factorial method to work, woefully few data are available on the true absorption of trace minerals. Because of antagonism to absorption (e.g., negative effect of S on absorption of Cu, Mn, Se, and Zn) equations will be needed to estimate AC under different dietary conditions, but current data are inaccurate to generate equations. The systems currently used will almost always prevent clinical mineral deficiencies, but because of uncertainties, most nutritionists formulate diets to exceed and often far exceed established recommendations. This leads to increased costs, potential antagonism, and increased manure excretion of environmentally important minerals. More accurate systems for estimating mineral requirements will optimize animal performance and health while keeping costs in check and reducing environmental damage.